Implementasi Algoritma Naïve Bayes Untuk Klasifikasi Sentimen Ulasan Pengguna KAI Access - Triana, Risma Faris; Sari, Ade Irma Purnama; Bahtiar, Agus; Wahyudin, Edi (STMIK Banjarbaru, 2025)
The internet have an important role in facilitating access to various applications, including KAI Access, which is designed to improve public transportation services. This application allows users to book tickets, check schedules, and get travel information efficiently. This study seeks to enhance the sentiment analysis model for user reviews by utilizing the Naïve Bayes algorithm. User review data taken from Google Play was preprocessed using TF-IDF technique to represent text as numerical vectors. Of the 1000 reviews analyzed, 965 reviews were processed and 35 reviews were deleted. The results showed negative sentiment (44.2%), followed by neutral (31.1%) and positive sentiment (24.7%). The Naïve Bayes algorithm produced an accuracy of 96.89% on the test data and 94.55% on the training data. These findings show that the Naïve Bayes algorithm is effective in classifying the sentiment of user reviews, providing important insights for improving the quality of app services.Keywords: Sentiment analysis; Naïve Bayes Algorithm; KAI Access; User reviews; TF-IDF AbstrakInternet berperan penting dalam memfasilitasi akses terhadap berbagai aplikasi, termasuk KAI Access, yang dirancang untuk meningkatkan layanan transportasi publik. Aplikasi ini memungkinkan pengguna memesan tiket, mengecek jadwal, dan mendapatkan informasi perjalanan secara efisien. Penelitian ini bertujuan meningkatkan model klasifikasi sentimen ulasan pengguna memakai algoritma Naïve Bayes. Data ulasan pengguna yang didapat dari Google Play diolah memakai praproses dengan teknik TF-IDF untuk merepresentasikan teks sebagai vektor numerik. Dari 1000 ulasan yang dianalisis, sebanyak 965 ulasan diproses dan 35 ulasan dihapus. Hasil penelitian menunjukkan sentimen negatif (44,2%), diikuti sentimen netral (31,1%) dan positif (24,7%). Algoritma Naïve Bayes menghasilkan akurasi 96,89% pada data uji dan 94,55% pada data latih. Temuan ini menegaskan jika algoritma Naïve Bayes sesuai ketika pengklasifikasian sentimen ulasan pengguna, memberi wawasan penting untuk memperbaiki performa layanan aplikasi.